The Fredholm alternative for the p-Laplacian in exterior domains. (September 2018) - Drábek, Pavel; Ho, Ky; Sarkar, Abhishek
Abstract: We investigate the Fredholm alternative for the p -Laplacian in an exterior domain which is the complement of the closed unit ball in R N ( N ≥ 2 ). By employing techniques of Calculus of Variations we obtain the multiplicity of solutions. The striking difference between our case and the entire space case is also discussed.